KEMAMPUAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN PENDEKATAN KETERAMPILAN PROSES - Anisa Nur Fadilah; Sigit Andi Prasetya Dinata; Hidayat Nur Septiadi (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This research aims to improve the ability to write descriptive text through a process skills approach in class VII students at SMP Darussalam Cimanggu. To find answers to these problems, the author conducted experimental research with a sample of 19 students. The research design used is one group Pre-Test Post-Test design. The sampling technique used was purposive sampling. The data collection technique used is through tests given to students before and after implementing the process skills approach learning. Next, the data was analyzed through descriptive statistics and inferential statistics with simple linear regression. Based on the research results, students' ability to write descriptive text through the process skills approach learning of class VII Darussalam Cimanggu Middle School, before implementing the process skills approach learning was categorized as less effective. This can be seen from the percentage of student learning outcomes obtained in the incomplete category of 84.2% and in the completed category of 15.78%, after applying the process skills learning approach it was categorized as effective. This can be seen from the percentage of results obtained in the completed category of 73.67% and the incomplete category and 26.30%. Based on the hypothesis testing carried out, applying the learning process skills approach has an influence on the learning outcomes of writing descriptive text for class VII students at Darussalam Cimanggu Middle School, which is obtained where F count = 11.605 is greater than F table = 0.000, meaning H1 is accepted and H0 is rejected.